Thinking Ecologically for Safer Healthcare: A Summer Research Student Partnership - Patricia Marck, Glenda Coleman-Miller, Carolyn Hoffman, Beth Horsburgh, Samantha Woolsey, Anila Dina, Tamara Dorfman, Jennifer Nolan, Naomi Jackson, Jennifer A. Kwan and Kathryn Hagedorn (Nursing Leadership, 2007)
As leaders for nursing education, nursing research, healthcare administration and patient safety, we asked one another: How do we use our collective resources to build health system capacity for clinically based research training and safer healthcare? Drawing on knowledge from the field of ecological restoration, which is the study and repair of damaged ecosystems, we partnered the Safer Systems research program of the Faculty of Nursing, University of Alberta, with Capital Health's Royal Alexandra Hospital (RAH), the Caritas Health Group, the Canadian Patient Safety Institute (CPSI) and several funding agencies to provide hands-on training in clinical research, infection control and patient safety policy development for nursing students during the summer months. As we plan ahead, our student and staff evaluations show that together, we can make concrete, vital contributions to student education, nursing research, evidence-informed practice, clinical quality improvement and national policy. We are using what we have learned to continually expand the range of undergraduate, graduate and post-doctoral clinical learning opportunities in healthcare safety that are available year round. Our shared goal is to support current and future nurses in leading the way for safer healthcare systems and the safest possible healthcare.
Keywords: patient safety, nursing education, nursing research, nursing practice, evidence-based care